Hepatic MCPIP1 protein levels are reduced in NAFLD patients and are predominantly expressed in cholangiocytes and liver endothelium - Natalia Pydyn; Justyna Kadluczka; Piotr Major; Tomasz Hutsch; Kinga Belamri; Piotr Malczak; Dorota Radkowiak; Andrzej Budzynski; Katarzyna Miekus; Jolanta Jura; Jerzy Kotlinowski (Hepatology Communications, 2023)
Background and Aims:. NAFLD is characterized by the excessive accumulation of fat in hepatocytes. NAFLD can range from simple steatosis to the aggressive form called NASH, which is characterized by both fatty liver and liver inflammation. Without proper treatment, NAFLD may further progress to life-threatening complications, such as fibrosis, cirrhosis, or liver failure. Monocyte chemoattractant protein-induced protein 1 (MCPIP1, alias Regnase 1) is a negative regulator of inflammation, acting through the cleavage of transcripts coding for proinflammatory cytokines and the inhibition of NF-κB activity. Methods:. In this study, we investigated MCPIP1 expression in the liver and peripheral blood mononuclear cells (PBMCs) collected from a cohort of 36 control and NAFLD patients hospitalized due to bariatric surgery or primary inguinal hernia laparoscopic repair. Based on liver histology data (hematoxylin and eosin and Oil Red-O staining), 12 patients were classified into the NAFL group, 19 into the NASH group, and 5 into the control (non-NAFLD) group. Biochemical characterization of patient plasma was followed by expression analysis of genes regulating inflammation and lipid metabolism. The MCPIP1 protein level was reduced in the livers of NAFL and NASH patients in comparison to non-NAFLD control individuals. In addition, in all groups of patients, immunohistochemical staining showed that the expression of MCPIP1 was higher in the portal fields and bile ducts in comparison to the liver parenchyma and central vein. The liver MCPIP1 protein level negatively correlated with hepatic steatosis but not with patient body mass index or any other analyte. The MCPIP1 level in PBMCs did not differ between NAFLD patients and control patients. Similarly, in patients’ PBMCs there were no differences in the expression of genes regulating β-oxidation (ACOX1, CPT1A, and ACC1) and inflammation (TNF, IL1B, IL6, IL8, IL10, and CCL2), or transcription factors controlling metabolism (FAS, LCN2, CEBPB, SREBP1, PPARA, and PPARG). Conclusion:. We have demonstrated that MCPIP1 protein levels are reduced in NAFLD patients, but further research is needed to investigate the specific role of MCPIP1 in NAFL initiation and the transition to NASH.